Preferential loan borrowers and the benefits of granting loans to agricultural companies in the Ma±opolska Region by Krakowski Bank Spó±dzielczy in 2004-2016 - Tomasz Tuteja (Economic and Environmental Studies (E&ES), 2018)
Contemporary agricultural companies are turning into complex businesses. Living in the countryside and running a holding is no longer a lifestyle but rather a business model aimed at manufacturing goods and bringing profit. In order to enhance their competitiveness, agricultural companies are getting more and more interested in external financing, mostly in preferential loans granted by cooperative banks. The study on the activity of Krakowski Bank Spó±dzielczy (Cooperative Bank of Cracow), granting loans to agricultural companies in the Ma±opolska Region in 2004-2016, showed that farmers with university degrees, including those in agricultural sciences, were the largest group granted preferential loans. The smallest group consisted of farmers with elementary education. Loans for building and modernising farms had the largest percentage share. Spending the money granted on preferential terms in a rational way had a positive impact on the production and economic efficiency of farms, contributing to an increase in their agricultural income and production, as well as fostering an increase in the production costs, which positively influenced the financial results of the companies.
Keywords: Q13; Q14; 330; agricultural holding; farm; cooperative banks; Krakowski Bank Spó±dzielczy; preferential loans; productive economic efficiency